Experimental studies on the quasi-static movements of tube sections filled with pumice stone. (2017) - Rajak, Dipen Kumar; Kumaraswamidhas, L.A.; Sahu, Sambit
Abstract: The present investigation on compressive deformation behaviour of aluminium sections filled with Pumice Stone (PS) has been studied. The load-displacement and energy absorption has been recorded. With the growing demand of infrastructure and structural engineering there has been always a need for light weight, recyclable structure which, this paper has aimed at. Traditional hollow metal sections are already being used in structural engineering whether it be civil or automobile. Idea is to give a better filled section alternative that can overcome all the flaws of traditional designing concept, and can give a new forward edge. Aluminium section width to thickness ratio is kept constant at 20.83. FE-SEM and EDX test has been conducted for knowing the compression behaviour, microscopic structure of the sample, its quality, and consistency of the sample.